Digital Human Resource Management: A Qualitative Study On Human Resource Transformation In The Era Of Artificial Intelligence - Drajat Sunaryadi (CV Pena Jaya Pers, 2026)
Purpose: This study aims to explore the transformation of Human Resource Management (HRM) through the implementation of Digital Human Resource Management (Digital HRM) in the era of Artificial Intelligence (AI). Design/methodology/approach: This study employed a qualitative case study approach. Data were collected through semi-structured interviews, observations, and document analysis involving HR managers and employees. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by data triangulation to ensure credibility. Findings: The findings indicate that Digital HRM supported by AI has transformed recruitment, employee development, performance management, and talent management. AI enhances operational efficiency, data-driven decision-making, and employee experience. However, successful implementation depends on organizational readiness, digital competencies, ethical AI governance, and effective change management. Research limitations/implications: This study is limited to a single case study. Future research is encouraged to examine multiple organizations and industries using comparative qualitative or mixed-method approaches. Practical implications: The findings provide insights for organizations in developing effective Digital HRM strategies while ensuring ethical AI implementation and sustainable human resource development. Originality/value: This study offers empirical evidence on how Artificial Intelligence supports Human Resource Management transformation and contributes to the growing literature on Digital HRM in the Industry 5.0 era.